Successful Management of Cervical Ectopic Pregnancy with Bilateral Uterine Artery Embolization and Methotrexate - Keitaroh Takeda (Case Reports in Emergency Medicine, 2018)
Cervical ectopic pregnancy (CEP) is a rare form of ectopic pregnancy. Cases diagnosed early in pregnancy can be managed medically, but more advanced pregnancies often require hysterectomy. Uterine artery embolization (UAE) is a novel approach to CEP for those who wish to preserve fertility. Here we present the case of a 44-year-old female with a 2-week history of vaginal bleeding and abdominal pain who was diagnosed with CEP and successfully treated with bilateral UAE (BUAE) in combination with methotrexate. A 44-year-old female presented to the emergency department with a 2-week history of vaginal bleeding. Serum beta-hCG was 71,964 mIU/ml. The transvaginal ultrasound confirmed CEP. The patient was referred to obstetrics and interventional radiology and ultimately treated with BUAE and methotrexate. Symptoms resolved quickly and she was discharged after 3 days.